2008
DOI: 10.1111/j.1468-1293.2008.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Switching from twice‐daily abacavir and lamivudine to the once‐daily fixed‐dose combination tablet of abacavir and lamivudine improves patient adherence and satisfaction with therapy

Abstract: Patients prefer fewer pills and once-daily (qd) dosing without food restrictions. We assessed the impact on adherence [by Medication Event Monitoring System (MEMS) cap monitoring] of switching from abacavir (ABC) and lamivudine (3TC) twice daily (bid) to ABC/3TC fixed-dose formulation (FDC, Kivexa s ) qd to achieve a qd regimen. MethodsA randomized, open-label, 8-week study comparing adherence, efficacy and safety of immediate vs. delayed switching from ABC/3TC to FDC qd. ResultsNinety-four patients were dosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Risk of bias assessments are summarized in Tables 2, 3 83 and one in which we judged the risk of bias to be high because some participants were allocated to the intervention arm without randomization. 82 Allocation concealment.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias assessments are summarized in Tables 2, 3 83 and one in which we judged the risk of bias to be high because some participants were allocated to the intervention arm without randomization. 82 Allocation concealment.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…39,47,78,79,82 Interventions. Based on the factors responsible for poor adherence, the interventions were categorized as patient related (n = 31), 36 37,62,63,69,83 social and economic factors (n = 1), 77 and condition related (n = 1). 44 The interventions in thirty-nine of these studies targeted only the patient; …”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, this study showed that ABC 600 mg QD and ABC 300 mg BID regimens led to similar intracellular CBV-TP C values, thus providing pharmacokinetic support for the interchangeability of these two regimens. Women had higher intracellular CBV-TP exposure than did men.Simplification of antiretroviral treatment (ART) by changing twice-daily (BID) regimens to once-daily (QD) regimens has been shown to contribute to better adherence and patient satisfaction (1,4,5,11,12,15,16), although differences in treatment outcome have not been commonly observed (5, 11). The decision to choose a QD regimen over a BID one, or vice versa, depends on the clinical situation.…”
mentioning
confidence: 99%
“…82 Switching from two separate NRTIs to combination pills has also shown to improve adherence and patient satisfaction. 83,84 Additionally, patients on NNRTI-based regimens have been shown in the past to have better adherence than those on PI-based regimens, likely at least in part due to the relatively low pill count and simplicity of NNRTI combinations, 85 though this has never been confirmed in a randomized trial. The importance of decreased regimen complexity and pill burden may be most important in those with significant social barriers to care.…”
Section: Adverse Effects and Prescribing Considerationsmentioning
confidence: 99%